Evaluation of Turkish Delight Prepared With Pigments And Essential Oils Extracted From Clementine (Citrus Clementine) Peels As Natural Antioxidants - Eman A. Ibrahim; Azza A. Omran; Zeinab A. Salama (مجلة بغداد للعلوم, 2022)
This experiment presented essential oils by GC/MS, pigment content, and their antioxidant activities as well as sensory evaluation of delight samples. Limonene (66.88%) was the most prevalent yield. The peels of clementine had DPPH and ABT Scavenging activity. All levels of pigment extract had better scores for all sensory values and recorded acceptable scores in terms of appearance, color, aroma, and overall acceptability compared to control delight. Besides, delight samples containing 15 mg astaxanthin pigment extract showed maximum sensory scores compared to other samples and control delight. On the other hand, the product was less acceptable to the panelists compared to control in the case of the addition of 3.75 mg astaxanthin pigment extract. All the analyzed samples showed that delight fortified with astaxanthin pigment which has high contents of essential oils has good antioxidant activities. As a general conclusion, Clementine peels are recommended as a useful value-added functional ingredient for the food industry as natural additives that will be healthier than artificial additives.